Chapter 12 Knowledge- policy nexus Policy research institutes and the urban development regime in Korea - Park, Se Hoon (Taylor & Francis, 2020)
There is an increasing tendency to use the development experience of Asian countries as a reference point for other countries in the Global South. Korea's condensed urbanization and industrialization, accompanied by the expansion of new cities and industrial complexes across the country, have become one such model, even if the fruits of such development may not have been equitably shared across geographies and generations. The chapters in this book critically reassess the Korean urban development experience from regional policy to new town development, demonstrating how these policy experiences were deeply rooted in Korea's socioeconomic environment and discussing what can be learned from them when applying them in other developmental contexts